Organic and Food Waste Management Mentoring on The LOSIDA Method in Tombatu I State Highschool, Southwestern Minahasa As a Manifestation of the P5 Program: Pendampingan Pengelolaan Sampah Organik dan Food Waste menggunakan Metode LOSIDA di SMA Negeri I Tombatu, Minahasa Tenggara sebagai Perwujudan Program P5 - Armstrong Fransiskus Sompotan; Johanna Zusye Wantania; Janne Deivy Ticoh; Revolson Alexius Mege; Livana Dethris Rawung; Dino Rahardiyan; Emma Mauren Moko (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Schools largely contributes to community wastes. Waste management movements are required to reduce impacts of community wastes. Tombatu 1 State Highschool, Southwestern Minahasa is a well recognized school in the vicinity. Their large studentbody are the biggest contributors to community local wastes. Losida (biopore) is a simple solution for managing organic waste by convertion to beneficial compost soil restoration on school grounds. The purpose of this activity was simple biopore application and management by teachers and students as a manifestation of the P5 program. Through this activity knowledge and skills of the students as a steward of the environment were honed. This activity serves a media for disemination and training inspiring students to grow for their love of the environment. Also, a media for science application of involved lecturers, impacting the society outside of campus grounds in the efforts of achieving on of the institution’s performance indicators (IKU Perguruan Tinggi).